2010
DOI: 10.3102/0013189x09357617
|View full text |Cite
|
Sign up to set email alerts
|

How Safe Are Our Schools?

Abstract: Schools are basically safe places for children. School violence and disruption, although in decline through the mid-to late 1990s, remains a concern. National surveys that inform research, policy, and practice have been designed for different purposes and can present conflicting findings. Common standards of risk and harm that could advance policy and practice are lacking. Progress in the field of school safety has been hindered by the lack of a coherent conceptual structure to guide measurement and research. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
32
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 49 publications
0
32
0
Order By: Relevance
“…Although young people are victims of serious violent crime less often in school than in other contexts (Mayer & Furlong, 2010), minor victimizations are common in schools. For example, accord-ing to the 2013 United States Youth Risk Behavior Survey, 8.1% of students in grades 9 through 12 reported having been involved in a physical fight on their school campus during the year preceding the survey, and 3.1% reported having been injured (i.e., injuries treated by a doctor or nurse) during these fights (Kann et al, 2014).…”
mentioning
confidence: 99%
“…Although young people are victims of serious violent crime less often in school than in other contexts (Mayer & Furlong, 2010), minor victimizations are common in schools. For example, accord-ing to the 2013 United States Youth Risk Behavior Survey, 8.1% of students in grades 9 through 12 reported having been involved in a physical fight on their school campus during the year preceding the survey, and 3.1% reported having been injured (i.e., injuries treated by a doctor or nurse) during these fights (Kann et al, 2014).…”
mentioning
confidence: 99%
“…These victimization rates were 18 crimes per 1,000 for students at school compared to 11 crimes per 1,000 for students away from school (Dinkes et al 2010). Mayer and Furlong (2010) found that the rate of violent victimization in schools was 32 per 1,000 students-a total that is much higher than the Dinkes et ai. (2010) results, demonstrating the variation in measurement and reporting for school victimization.…”
Section: Statement Of Problemmentioning
confidence: 70%
“…Females reported fewer instances of theft and violent victimization (8 per 1,000) away from schools compared to their male classmates (14 per 1,000) (Dinkes et aI., 2010). Mayer and Furlong (2010) found that males (32 per 1000) had a higher victimization rate than females (25 per 1000) in regard to sexual victimization, robbery, assault, and aggravated assault. Females also reported fewer instances of violent altercations and weapons possession while in the school environment (Dinkes et aI., 2010).…”
Section: Statement Of Problemmentioning
confidence: 96%
See 2 more Smart Citations